PERANAN MOTIVASI DALAM MEMPENGARUHI KEPUASAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA RUMAH SAKIT ORTOPEDI PROF. DR. R. SOEHARSO SURAKARTA - Astuti, Ester Dwi; -, Mulyanto - (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2013)
This research aims to test: 1) the influence of a job satisfaction toward the employees motivation, 2) the influence of a job discipline toward the employees motivation, 3) the influence of a job satisfaction toward the employees performance, 4) the influence of a job discipline toward the employees performance, 5) the influence of a motivation toward the employees performance. The data are collected from 120 employees by using a accidental sampling. They are analyzed through the research instruments such as the validity test by using a product moment test and the reliability test by using a Cronbach Alpha technique; linearity test by using Langrange Multiplier test; the hypothesis test such as: path analysis, t test, F test and determination coefficient (R2); correlation between variable and than direct effect and indirect effect. The research result shows that: 1) the influence of a job satisfaction positive significant toward the employees motivation, 2) the influence of a job discipline positive significant toward the employees motivation, 3) the influence of a job satisfaction insignificant toward the employees performance, 4) the influence of a job discipline positive significant toward the employees performance, 5) the influence of a motivation positive significant toward the employees performance, 6) the role of motivation on influence job satisfaction and job discipline toward the employees performance and while its explained by other factors which are involved in the regression model such as a job culture and education. Keywords: job satisfaction, job discipline, motivation, employees performance